A Multi-Institutional Randomized Controlled Trial to Investigate Whether Zoledronate Prevents Bone Loss After Discontinuation of Denosumab: The Study Protocol of Denosumab Sequential Therapy (DST) Trial - Lee, Chia-Che; Wang, Chen-Yu; Hung, Chih-Chien; Huang, Chuan-Ching; Li, Chung-Yi; Chen, Hsuan-Yu; Chang, Yun-Liang; Tseng, Wo-Jan; Wang, Ting-Ming; Yang, Rong-Sen; Wong, Tze-Hong; Fu, Shau-Huai (Frontiers in Medicine, 2021)
Background: The rebound effect after discontinuation of denosumab in patients with osteoporosis has drawn investigators’ attention. It includes a dramatic loss of gained bone mineral density (BMD) and an increased risk of vertebral fractures. This prospective multi-institutional randomized controlled trial aims to investigate whether zoledronate prevents loss of BMD after the discontinuation of denosumab. The trial was registered as Denosumab Sequential Therapy (DST) trial in March 2019 at clinicaltrials.gov, with the identifier NCT03868033. Methods: The study is conducted at National Taiwan University Hospital and its branches. Patients without history of exposure to other anti-osteoporotic medications than denosumab, who had continuously received denosumab treatment for 2 or more years, are surveyed for eligibility. Baseline characteristics and questionnaires of life quality are recorded after recruitment. BMD, circulating levels of bone turnover markers (BTMs), including serum N-terminal propeptide of type 1 collagen (P1NP) and C-terminal telopeptide (CTX), are checked before the stratified randomization to 4 groups. The participants in group 1 continue denosumab therapy for another 2 years. All the other patients receive zoledronate in the first year. The participants in group 2, 3, and 4 have denosumab, zoledronate and drug holiday in the second year, respectively. Annual level of BMD and pre-scheduled checkpoints of bone turnover markers will be checked. For patient safety, rescue treatment with another injection of zoledronate would be applied to the patients in group 4 if the CTX levels raise above the prespecified threshold, 0.573 ng/mL for women and 0.584 ng/mL for men, during the drug holiday. The primary outcomes are the differences in BMD changes of lumbar spine, total hip and femoral neck. The secondary outcomes included the differences of serum level changes in BTMs, the incidence of new osteoporotic fractures, extra zoledronate injections needed in group 4 and the differences in the quality of life. Discussion: We aim to provide evidence whether zoledronate prevents bone loss after demosumab cessation. To our knowledge, the study has the largest sample size. No other randomized controlled study included the three different treatment strategies and a positive control. It is also the first associated randomized controlled trial outside Europe.